Obstetrics by ten teachers - Baker, Philip N.; Kenny, Louise C. (Hodder Arnold, 2011)
First published in 1917 as 'Midwifery', Obstetrics by Ten Teachers is well established as a concise, yet comprehensive, guide within its field. The nineteenth edition has been thoroughly updated, integrating clinical material with the latest scientific advances. With an additional editor and new contributing authors, the new edition combines authoritative detail while signposting essential knowledge. Retaining the favoured textual features of preceding editions, each chapter is highly structured, with overviews, definitions, aetiology, clinical features, investigation, treatments, key points and additional reading where appropriate. Together with its companion Gynaecology by Ten Teachers, the volume has been edited carefully to ensure consistency of structure, style and level of detail, as well as avoiding overlap of material. For almost a century the 'Ten Teachers' titles have together found favour with students, lecturers and practitioners alike. The nineteenth editions continue to provide an accessible 'one stop shop' in obstetrics for a new generation of doctors.